SKI‐G‐801, an AXL kinase inhibitor, blocks metastasis through inducing anti‐tumor immune responses and potentiates anti‐PD‐1 therapy in mouse cancer models. Issue 1 (29th December 2021) - Synn, Chun‐Bong; Kim, Sung Eun; Lee, Hee Kyu; Kim, Min‐Hwan; Kim, Jae Hwan; Lee, Ji Min; Jo, Ha Ni; Lee, Wongeun; Kim, Dong Kwon; Byeon, Youngseon; Kim, Young Seob; Yun, Mi Ran; et al.
Abstract: Objectives: AXL‐mediated activation of aberrant tyrosine kinase drives various oncogenic processes and facilitates an immunosuppressive microenvironment. We evaluated the anti‐tumor and anti‐metastatic activities of SKI‐G‐801, a small‐molecule inhibitor of AXL, alone and in combination with anti‐PD‐1 therapy. Methods: In vitro pAXL inhibition by SKI‐G‐801 was performed in both human and mouse cancer cell lines. Immunocompetent mouse models of tumor were established to measure anti‐metastatic potential of SKI‐G‐801. Furthermore, SKI‐G‐801, anti‐PD‐1 or their combination was administered as an adjuvant or neoadjuvant in the 4T1 tumor model to assess their potential for clinical application. Results: SKI‐G‐801 robustly inhibited pAXL expression in various cell lines. SKI‐G‐801 alone or in combination with anti‐PD‐1 potently inhibited metastasis in B16F10 melanoma, CT26 colon and 4T1 breast models. SKI‐G‐801 inhibited the growth of B16F10 and 4T1 tumor‐bearing mice but not immune‐deficient mice. An antibody depletion assay revealed that CD8 + T cells significantly contributed to SKI‐G‐801‐mediated survival. Anti‐PD‐1 and combination group were observed the increased CD8 + Ki67 + and effector T cells and M1 macrophage and decreased M2 macrophage, and granulocytic myeloid‐derived suppressor cell (G‐MDSC) compared to the control group. The neoadjuvant combination of SKI‐G‐801 and anti‐PD‐1 therapy achieved superior survival benefits by inducing more profound T‐cell responses in the 4T1 syngeneic mouse model. Conclusion: SKI‐G‐801 significantly suppressed tumor metastasis and growth by enhancing anti‐tumor immune responses. Our results suggest that SKI‐G‐801 has the potential to overcome anti‐PD‐1 therapy resistance and allow more patients to benefit from anti‐PD‐1 therapy. Abstract : SKI‐G‐801, a novel AXL inhibitor, significantly suppressed tumor metastasis and growth by enhancing anti‐tumor immune responses. Our results suggest that SKI‐G‐801 has the potential to overcome resistance to anti‐PD‐1 therapy and expand the number of patients who benefit from anti‐PD‐1 therapy.